Prioritization of needs among students of University of Medical Sciences: A needs assessment - Esmaeil Fattahi; Mahnaz Solhi; Jaffar Abbas; Parisa Kasmaei; Sedighe Rastaghi; Mahnaz Pouresmaeil; Arash Ziapour; Hadi Darvishi Gilan (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The need assessment is a fundamental part of any planning, and almost by neglecting it, the effectiveness of the programs is impossible. The purpose of this study was the prioritization of needs among students of the Iran University of Medical Sciences. MATERIALS AND METHODS: The design study was conducted in two parts; in the first part, the design of the questionnaire was done by qualitative methods. The questionnaires were extracted by interviewing and obtained acceptable validity and reliability. Moreover, the second part created a questionnaire consisting of four categories: education, welfare, economic, and psychological and social. A simple random sampling method was used to select 363 people using the Cochran formula. Finally, 336 people (including 28 people excluded) completed the questionnaire. A questionnaire designed to collect sample data was used and analyzed using version 23 of SPSS. RESULTS: A total of 336 students (26.77 ± 5.45 years) participated in the study. 123 (36.6%) were male and 213 (63.4%) were female. Psychological and social needs of students were prioritized, and educational priorities were ranked second. The findings showed that there was no significant statistical difference between the scores of welfares and psychosocial and educational needs and the gender of the research units (P > 0.05). However, in the mean of economic needs scores, there is a significant statistical difference between the marital status of the research units (P < 0.05). CONCLUSION: The results of our study in the research units showed that the priority of psychosocial needs was more than other needs and the educational priority was the next. According to the results of this study, we suggest that, in future educational and educational planning, policymakers and planners should pay attention to psychological and social issues.